(untitled) (Research, Society and Development, 2021)
Aim: the present study carried out an integrative review aiming to evaluate the chemical aspects of species belonging to the Costus genus, as well studies that evaluated the biological activities. Methods: Initial bibliographic survey in PUBMED and SCOPUS, using strings “Costus AND medicine pharmacological”. Titles and abstracts were read and selected according to eligibility criteria. In the second stage, the articles were full read and articles that did not meet the inclusion criteria were excluded. Results: Twenty-one articles were included, relating to phytochemical information and different biological activities. Species of the Costus have shown promising activities for the treatment of inflammation, pain, diabetes and nephrolithiasis, in connection with some claims of popular use. Final considerations: In summary, species belonging to the genus Costus are promising in medicinal terms, requiring further tests to assess the safety of the compounds present in the species of the genus for future clinical trials.